Deep breathing relaxation with guided imagery on pain intensity and vital signs of post-caesarean section patients with a Comfort Theory approach - Diah Priyantini; Daviq Ayatulloh; Nursalam Nursalam (Majalah Obstetri & Ginekologi, 2026)
HIGHLIGHTS The combination of deep breathing relaxation therapy with guided imagery is an effective non-pharmacological therapy for post-caesarean section patients. The combined intervention of deep breathing relaxation with guided imagery based on the Comfort Theory approach has an impact on the pain intensity of post-caesarean section patients.   ABSTRACT Objective: This study aimed to evaluate the effect of combining deep breathing relaxation techniques with guided imagery on pain intensity and vital signs in patients following caesarean section. Materials and Methods: A quasi-experimental study was conducted among mothers who had undergone caesarean section. A total of 40 respondents were allocated into an intervention group (n=20) and a control group (n=20) using purposive sampling. The independent variable was deep breathing relaxation combined with guided imagery based on Comfort Theory, whereas the dependent variables were pain intensity, assessed using the Numerical Rating Scale, and vital signs (TTV), including blood pressure, pulse rate, and respiratory frequency, measured using examination and observation sheets. Data were analyzed using paired t-tests and independent t-tests. Results: In the intervention group, the intervention significantly affected systolic blood pressure, diastolic blood pressure, pulse rate, and pain intensity (p<0.05). The greatest improvement was observed in systolic blood pressure (Δ=15.75), followed by diastolic blood pressure (Δ=4.25), pulse rate (Δ=3.80), and pain intensity (Δ=2.40). Between-group analysis after the intervention demonstrated significant differences in systolic blood pressure (p=0.000), pulse rate (p=0.009), respiratory frequency (p=0.004), and pain intensity (p=0.000), whereas diastolic blood pressure did not differ significantly between the groups (p=0.126). Conclusion: Deep breathing relaxation combined with guided imagery based on Comfort Theory effectively reduced pain intensity in patients following caesarean section, as demonstrated by a reduction in pain scores from 5–7 to 1–3. The intervention also improved patients' vital signs by reducing systolic and diastolic blood pressure as well as pulse rate.